Compact collimators designed with point approximation for light-emitting diodes. (April 2018) - Luo, T; Wang, G
We present a novel freeform lens design method for application to light-emitting diode collimating illumination. The lens is designed with a point-source assumption to form compact collimators. The method is derived from a basic geometric-optics analysis and the associated construction approach. By using this method, a compact collimating lenses with an aspect ratio = 0.181 is developed. With optimization of initial parameters, a highly collimating lens for a Cree XP-E LED (chip size: 1.2 mm × 1.2 mm) with an optical efficiency of 88.5% under a beam angle of ± 1.9° is constructed by simulation. To verify the practical performance of the lens, a prototype of the collimator lens is also made. This has light distribution compatible with the simulation results.